Screening and Determination of Opiates in Human Urine Samples by Immunoassay and TLC-Spectrophotodensitometry - Dewi, Ni Putu Diah Kusuma; Indayanti, Ni Wayan Intan; Sanjaya, I Komang Niko; Dewi, Anak Agung Intan Kharisma; Laksmiani, Ni Putu Linda (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2020)
Opiates are a class of substances, both natural and semisynthetic that have the ability to relieve pain (analgesics), put to sleep (hypnotics), and cause feelings of joy (euphoric). Repeated use will lead to tolerance (immunity to substances) and dependence. Therefore opiate class compounds besides can be used in medicine, are also very vulnerable to abuse. So that we need a method to detect the presence of opiates in biological specimens, one of which is in the urine. In this study, testing of simulated samples that have been added with certain narcotic compounds. The process of screening of compounds in the urine can be done using the immunoassay technique with a strip test. The test results showed positive for opiates. Confirmation test using TLC Spectrophotodensitometry in the TE mobile phase system (ethyl acetate: methanol: ammonia 85: 10: 5% v/v/v) and the mobile phase TAE (methanol 100% v / v) shows the confirmation of the content of opiate compounds in urine samples simulation is morphine. The next step is the determination test with TLC Spectrophotodensitometry in the TE motion system (ethyl acetate: methanol: ammonia 85: 10: 5% v/v/v) using six series solutions with different concentrations (100, 300, 500, 700, 900, and 1100 ng / µL). The resulting correlation coefficient is 0.9762, LOD is 493.24 ng, and LOQ is 1494.66 ng. In the simulation urine sample morphine levels were 25.55 ?g / mL, 17.56 25.55 ?g / mL, and 14.96 25.55 ?g / mL at three replications. Opiates are a class of substances, both natural and semisynthetic that have the ability to relieve pain (analgesics), put to sleep (hypnotics), and cause feelings of joy (euphoric). Repeated use will lead to tolerance (immunity to substances) and dependence. Therefore opiate class compounds besides can be used in medicine, are also very vulnerable to abuse. So that we need a method to detect the presence of opiates in biological specimens, one of which is in the urine. In this study, testing of simulated samples that have been added with certain narcotic compounds. The process of screening of compounds in the urine can be done using the immunoassay technique with a strip test. The test results showed positive for opiates. Confirmation test using TLC Spectrophotodensitometry in the TE mobile phase system (ethyl acetate: methanol: ammonia 85: 10: 5% v/v/v) and the mobile phase TAE (methanol 100% v / v) shows the confirmation of the content of opiate compounds in urine samples simulation is morphine. The next step is the determination test with TLC Spectrophotodensitometry in the TE motion system (ethyl acetate: methanol: ammonia 85: 10: 5% v/v/v) using six series solutions with different concentrations (100, 300, 500, 700, 900, and 1100 ng / µL). The resulting correlation coefficient is 0.9762, LOD is 493.24 ng, and LOQ is 1494.66 ng. In the simulation urine sample morphine levels were 25.55 ?g / mL, 17.56 25.55 ?g / mL, and 14.96 25.55 ?g / mL at three replications.